PENGARUH KUALITAS KEHIDUPAN KERJA, KEPUASAN KERJA DAN KOMITMEN KARYAWAN TERHADAP KINERJA KARYAWAN TERHADAP KINERJA KARYAWAN DAN PRILAKU KEWARGAAN SEBAGAI VARIABEL INTERVENING (STUDI PADA PT. PERINDUSTRIAN DAN PERDAGANGAN CRUMB RUBBER PEKANBARU) - Erick Robson Lumbantoruan; Marnis '; Nuryanti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The purpose of this study was to examine the influence of Influence Quality of working life, job satisfaction and employee commitment to Performance aganizational Citizenship Behavior as an intervening variable in PT. Crumb Rubber Industry and Trade Pekanbaru in 2009 to 2013. Random sampling method is used to determine our samplengs. Of the 365 field employees, 108 employees were taken as samples. For the analysis of this data using network analysis / path analisisbe. T-test, F-test, and determine coefficient were used to test our hypotheses. The results of this research show that each dependent variable; quality of work life, job satisfaction, employee commitment is significant positive effect on performance. Assessed in relation to the dependent variable, it directly influences the dependent variable (quality of work life, job satisfaction, employee commitment) greater employee on the performance of the indirect effect through intervening variables (organizational citizenship behavior). And the quality of working life is a variable that has the most significant effect on the comparison of direct and indirect influence on performance.Keywords: Quality of work life, job satisfaction, employee commitment, organizational citizenship behavior, employee performance.